Carotid-femoral pulse wave velocity and strain echocardiography in neonates: impact of maternal diabetes and hypertension - Mercan, Umut Berk; Yiğit, Şule; Karagöz, Tevfik; Aykan, Hayrettin Hakan (The Turkish Journal of Pediatrics, 2026)
Background. The arterial wall tends to stiffen owing to prolonged exposure to cardiovascular disease risk factors such as high blood pressure, hyperglycemia, and chronic inflammation. Epidemiological research has demonstrated that maternal factors, demographic characteristics, and clinical data influence arterial stiffness and echocardiographic findings. This study aimed to evaluate the association between arterial stiffness and echocardiographic findings with maternal factors and demographic and clinical characteristics in infants of mothers with gestational diabetes or hypertension during the neonatal period.Methods. A total of 67 newborns between 12-29 days of age, including 15 neonates of hypertensive mothers, 26 neonates of diabetic mothers, and 26 neonates in the control group, were included. Carotid-femoral pulse wave velocity (cfPWV) was used as a marker of arterial stiffness and measurements were performed using echocardiography. Basic echocardiographic evaluations and atrial and ventricular strain assessments were performed.Results. The mean cfPWV value of infants of diabetic mothers (6.34 m/s) was significantly higher than that of infants of hypertensive mothers (4.65 m/s) and the control group (4.56 m/s) (p
Keywords: neonates; gestational diabetes mellitus (GDM); gestational hypertension; arterial stiffness; strain echocardiography; relative wall thickness